Performance and Usability Assessment of Recycled Aggregate Extracted from Demolished Concrete Subjected to Multiple Recycling - Md Roknuzzaman; Md Rahman; Md Islam (Journal of Rehabilitation in Civil Engineering)
Concrete recycling is a growing trend in sustainable construction that aims to protect natural ingredients and reduce waste generation. However, most research focuses on first-generation recycled aggregates, and further evidence of recycled green concrete's potential for reuse is required. This investigation aims to evaluate the quality of aggregates through multiple recycling cycles and its impact on green concrete performance. Concrete blocks collected from a demolished highway culvert are broken into standard aggregate sizes. Green concrete prepared using these recycled aggregates is named first-generation green concrete. After attaining sufficient strength, the first-generation green concrete is broken to produce aggregates, which are said to be second-generation recycled aggregates, and concrete made with them as second-generation green concrete. In a similar manner, third and fourth-generation recycled aggregate and green concrete specimens are produced. Some quality parameters of aggregate, such as water absorption, aggregate crushing value (ACV), and Log Angeles abrasion resistance (LA), are monitored after each cycle of recycling. A maximum of 2nd generation recycled aggregates met the quality requirements of standard aggregates for concreting with an ACV of 27% (<30%) and LA of 39% (<40%). The compressive strength of green concrete built from first- to fourth-generation recycled aggregates is measured and investigated. The patterns of strength increase and loss are exhibited after each generation of recycling. It has been found that the first-generation green concrete may be useful as structural concrete in grades C-20 and C-25, while the second and third generation green concrete may be utilized for low-load bearing structures if longer curing is assured.